정신건강문제를 중재한 수용전념치료 연구에 대한 통합적 문헌고찰 - 최덕자(Dugja Choi); 김성재(Sungjae Kim) (Seuteureseu yeon-gu (Online), 2017)
본 연구는 국내 수용전념치료 연구를 통합적으로 고찰하여 치료의 효과성과 임상적 유용성을 파악하고, 이를 근거로 향후 연구 방향과 효과적인 프로그램 구성 및 전략을 제시하고자 시도하였다. 연구결과, 대상자의 특성과 연구 목적에 따라 수용전념치료의 6가지 핵심 원리를 유연하게 구성하는 것이 중요 전략임을 확인하였다. 즉, 불안은 기꺼이 경험하기와 인지적 탈융합을 강조하고, 우울은 자기자비와 자기수용에 초점을 두며, 중독은 비효과적인 대처 감소를 위해 전념행동에 중점을 두고, PTSD는 현재에 존재하기에 역점을 두어 중재하는 것이 효과적이었다. 수용전념치료는 저항적이고 만성화 경향이 있는 정신건강문제에 효과적인 중재가 될 수 있으므로, 조현병이나 양극성 장애를 위한 수용전념치료 프로그램의 개발이 필요하다. The purpose of this study was to provide an integrative review of ACT for mental health problems to identify content of program and discuss methodological strategy of intervention according to target population. According to Whittmore and Knaf's integrative review method, this research was conducted in five stages: clarification of research problems, literature search, and quality evaluation of data, data analysis, and data description. The key words in English and Korean were used to search through seven electronic databases. 21 studies were finally included in this integrative review. ACT was used as an intervention for anxiety, depression, posttraumatic stress disorder and eating disorders and was effective in social avoidance, anxiety sensitivity, depression, dysfunctional belief and negative thinking. It was also used as an intervention for the maladjustment in adolescence to improve self-esteem and reduce behavioral problem. The six core processes of ACT are useful for people with chronic mental illness who have an ineffective avoidance strategy that avoids their symptoms and does not accept the illness. We give a suggestion that researchers develop and apply appropriate ACT for mentally ill person in hospitals. KCI Citation Count: 10